The SRG/eROSITA diffuse soft X-ray background: I. the local hot bubble in the western Galactic hemisphere - Yeung, Michael C.H.; Ponti, Gabriele; Freyberg, Michael J.; Dennerl, Konrad; Liu, Teng; Locatelli, Nicola; Mayer, Martin; Sanders, Jeremy S.; Sasaki, Manami; Strong, Andy; Zhang, Yi; Zheng, Xueying; et al. (Astronomy & Astrophysics, 2024)
Context. The SRG/eROSITA All-Sky Surveys (eRASSs) combine the advantages of complete sky coverage and the energy resolution provided by the charge couple device and offer the most holistic and detailed view of the diffuse soft X-ray background (SXRB) to date. The first eRASS (eRASSl) was completed at solar minimum, when solar wind charge exchange emission was minimal, providing the clearest view of the SXRB. Aims. We aim to extract spatial and spectral information from each constituent of the SXRB in the western Galactic hemisphere, focusing on the local hot bubble (LHB). Methods. We extracted and analysed eRASSl spectra from almost all directions in the western Galactic hemisphere by dividing the sky into equal signal-to-noise bins. We fitted all bins with fixed spectral templates of known background constituents. Results. We find the temperature of the LHB exhibits a north-south dichotomy at high latitudes (|b| > 30), with the south being hotter, with a mean temperature at kT = 121.8 ± 0.6 eV and the north at kT = 100.8 ± 0.5 eV. At low latitudes, the LHB temperature increases towards the Galactic plane, especially towards the inner Galaxy. The LHB emission measure (EMLHB) enhances approximately towards the Galactic poles. The EMLHB map shows clear anti-correlation with the local dust column density. In particular, we found tunnels of dust cavities filled with hot plasma, potentially forming a wider network of hot interstellar medium. We also constructed a three-dimensional LHB model from EMLHB, assuming constant density. The average thermal pressure of the LHB is Pthermal/k = 10100-1500+1200 cm-3 K, a lower value than typical supernova remnants and wind-blown bubbles. This could be an indication of the LHB being open towards high Galactic latitudes.
CRIS-Team Scopus Importer:2024-11-15
Keywords: ISM: bubbles; ISM: structure; Local insterstellar matter; Solar neighborhood; X-rays: diffuse background; X-rays: ISM